Preparation and Characterization of the Flexible Polypyrrole Film with High Density - Chen, Feng; Peng, Xianghong (Asian Journal of Chemistry, 2014)
High density polypyrrole (Ppy) films show higher thermal deposition temperature and better electrochemical stability under long oxidative polarization. The high density polypyrrole films is usually synthesized at low temperature (-40 °C). In this paper, the high density polypyrrole film has been prepared by the two electrode method at room temperature by simple method. The structures and the morphologies of polypyrrole film are characterized by FTIR, Raman, TGA and SEM. The density and the cyclic voltammetry of polypyrrole film are measurement. The density of polypyrrole film is 1.17 g/cm3 and 1.03 g/cm3 with the current density of 1 and 5 mA/cm2, respectively. The polypyrrole film can be folded 180º for 20 times without mark. The film exhibit a more homogeneous surface with semimicrosphere and cauliflower microspheres on the side. The cyclovoltametric curves show no peaks, indicating that the polypyrrole film is a kind of excellent electrode material in double-layer capacitance. The high density polypyrrole film with flexible may be potential applications in the field of the flexible supercapacitor electrodes.